2020
DOI: 10.1371/journal.pone.0231869
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive-resistive radiofrequency therapy to treat postpartum perineal pain: A randomized study

Abstract: ObjectiveTo evaluate the reduction of perineal pain after vaginal deliveries by capacitive resistive radiofrequency therapy (RF). MethodsWe conducted a double-blind randomized study in University Hospital Centre in France. We included women presenting either perineal tears or an episiotomy after vaginal delivery (instrumental assisted or not). The participants were randomly assigned to RF or not at day 1 and day 2 postpartum. The primary outcome was pain evaluated as visual analog scale (VAS) score >4 at rest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 24 publications
1
18
1
1
Order By: Relevance
“…The title and abstract of the remaining 578 were screened and 463 were excluded due to the selection criteria. In the end, 100 more studies were excluded after reading the whole text, obtaining 15 studies that met the inclusion criteria [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The title and abstract of the remaining 578 were screened and 463 were excluded due to the selection criteria. In the end, 100 more studies were excluded after reading the whole text, obtaining 15 studies that met the inclusion criteria [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The randomized controlled trials that were selected obtained moderate quality on the PEDro scale: three scored 5/10 [ 20 , 27 , 29 ], one 6/10 [ 21 ] and the last 7/10 [ 28 ]. These results suggest that higher quality randomized controlled trials are necessary on this topic, as the existing studies present several limitations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found no significant differences in pain or medication intake. However, there was a reduction in discomfort during sitting, presenting a prevalence within the treatment group of 12% ± 41.1% compared with the placebo group (20% ± 64.5%) [ 18 ]. Likewise, childbirth has been shown as one of the possible causes of dyspareunia [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…RF procedures in chronic pain utilize alternating current in the AM RF band to produce effects on pain pathways[18](Rea et Al 2011). In 2020 Bretelle y Col[19] …”
mentioning
confidence: 99%